Microbiological profile of urinary tract infection associated with type-2 diabetes - DORIN DSOUZA; N. LAKSHMIDEVI (International Journal of Pharma and Bio Sciences, 2017)
Microbial complication associated with diabetes mellitus is of concern and the Multi drug resistant organisms (MDRO’s) prevailing in these infections assumes its significance. The present study aimed to determine the microbial etiology and the drug resistance patterns of the pathogens implicated in urinary tract infections in diabetic patients. Mid- stream urine samples were collected, processed and identified as per CLSI guidelines. Bacterial susceptibility testing was performed by disc diffusion method and in vitro presence of Methicillin-resistant Staphylococcus aureus (MRSA) and Extended-spectrum beta-lactamases (ESBL) was confirmed as per CLSI guidelines. The major bacterial pathogens in Urinary Tract Infections (UTI) were E. coli followed by K. pneumoniae and S. aureus. E. coli, the predominant isolate of UTI was highly resistant to amoxyclav (27.4%), doxycycline HCl and cefotaxime (20.8%) and least resistant to levofloxacin (4.3%) and imipenin (5.4%). Among the total E. coli isolates 30.76% (16 out of 52) were ESBL producers and 44.44% of K. pneumoniae (8 out of 18) were ESBL producers. In conclusion, the emergence of multidrug resistant bacterial strains complicates microbial infections. The resistance of ESBL-positive organisms to commonly used antibiotics carries a major concern and limits their usage in treating conditions like UTI in individuals with diabetes.